Relationship between Academic Adjustment among Married Female Students and Levels of Marital Stability, in the Light of the Role Theory - bent Hammad bin Mohsen Alrashidi, Anwar (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
The present study aimed to investigate the relationship between academic adaptation among married female students and levels of marital stability, in the light of the role conflict theory. The sample of the study consisted of (60) female students from Prince Sattam bin Abdulaziz University. The researcher adopted the correlational descriptive approach and using on the Academic Adaptation Scale and Marital Stability Scale to achieve the study's objectives. The study obtained several findings, most importantly the following: Academic adaptation, in light of the (role conflict) theory, among married female students, was rated (high), from the perspectives of sample members; Marital stability, in light of the (role conflict) theory, among married female students, was rated (high), from the perspectives of sample members; and the existence of a positive correlation between the total score for marital stability and the dimensions of academic adaptation and its total score. In light of these findings, the researcher presents several recommendations, most importantly the following: The necessity of providing more training courses for girls who are about to get married to educate them on how to achieve family stability; and the necessity of partnership between community training institutions and Saudi universities in order to determine the needs of married female students for continuing their academic lives and achieve their goals through them.